“I have chosen to look at those dying this way as if they are dying from a disease”: Perceptions of suicide and their possible effects on bereavement - Silke Schurack 1975- (2018)
In the context of sudden death, such as suicide, aspects of our personal and society’s general understanding and attitude towards lives and deaths and the historical context of which they are created, are mirrored in the sense making of the (more often than not) utterly upsetting event. Potential agency to act upon whatever life throws at us, how things affect us, and how we respond to emotional stress – including help seeking behavior and possible barriers encountered on the way to recovery, is bound to our habitus. That is, our “second nature”, a composition of our social, cultural, and political environment, as well as personal experiences. Moreover, the event can be turned into a new beginning, re-arranging life, adding new perspectives, and changing attitudes. Shifting from being acted upon into an actor, even feeling of being able to act upon the very event, or even the phenomenon as such, which appears larger after affecting us directly, gives back some sense of control, which is suggested to be essential to well-being and health, and recovery after loss. With a mixed approach of qualitative and quantitative data collection, this study maps out the experiences of those bereaved by suicide regarding available help in Iceland and matched with the aforementioned considerations. Við skyndilegt dauðsfall, svo sem sjálfsvíg, endurspeglast eigin skilningur og samfélagsins á lífi og dauða og sögulegu samhengi þess í viðbrögðum okkar við þeim (oftar en ekki) gjörsamlega óskiljanlega atburði og tilraunir til að fá botn í aðstæður. Getan til að bregðast við hverju því sem lífið beinir að okkur, leggur fyrir okkur, hvernig atburðir hafa áhrif á okkur og hvernig við bregðumst við tilfinningalegu álagi – þar með talið hvernig við leitum eftir aðstoð sem og mögulegar hindranir sem verða á vegi okkar í bataferlinu -- fer eftir ástandi okkar. Þ.e. (vana) eðlislægri hegðun og samblandi af félagslegu, menningarlegu og stjórnmálalegu umhverfi, sem og reynslu hvers og eins. Þau umskipti, að fara frá því að vera sá/sú sem ...